IMPLEMENTASI SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) DI SEKRETARIAT PANWASLIH KABUPATEN ACEH SINGKIL - Zuraidah Zuraidah; Lisnawati Lisnawati (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2025)
This study aims to determine how the implementation of the Agency Level Financial Application System (SAKTI) is financial management at the Panwaslih Secretariat of Aceh Singkil Regency. Data collection techniques using observation, interviews and documentation. The data analysis technique used in this study is qualitative descriptive analysis. Based on the research results, it is known that the SAKTI application has been established since 2022 and in implementing is application, authorized employees expect special training from the government and not only training through social media so that its implementation can be carried out more optimally. In order to improve Financial Management at Panwaslih, accourding to the results of the study, the SAKTI Applicarion cannot guarantee the risk of errors in the administration module related to the management of reference data and SAKTI user data. Keywords: Implementation, SAKTI Application, Financial Management